Ruminal degradability evaluations of green forages by nylon-bag technique - KALBANDE, V H; THOMAS, C T (The Indian Journal of Animal Sciences, 2013)
Five green roughages, viz. maize (Zea mays), sorghum (Sorghum Bicolor) and guinea (Panicum maximum), para (Brachiaria mutica) and napier grass (Pannisetum purpureum), commonly used in cattle rations were tested for their dry matter and nitrogen disappearance rates at different intervals of incubation in the rumen of crossbred cows by nylon-bag technique. The percentage disappearance rates at 48 hr of incubation for DM were 76.2±0.9, 77.4±0.4, 57.0±2.2,67. 2±0.6 and 64.4±0.8 and for N were 77. 7±0.21, 78.2±0.3, 64.3±0.8, 67.6±1.8 and 75.2±2.9 for green maize, sorghum and guinea, para and napier grass, with their effective protein degradabilities estimated at the rumen outflow rate ofO.05/hr were·56.93, 58.80,35.74,45.39 and 36.68% respectively. Maize and sorghum fodders contained more soluble and degradable DM and N than different green grasses studied. Among the 3 grasses, guinea grass appeared a better source of undegradable dietary protein(UDP)/bypass protein as compared to either napier or para grass.